COMPARISON OF JUVENILE JUSTICE SYSTEMS IN INDONESIA AND SOUTH KOREA - Oktaviani, Adelia; Romadhon, Satrio Fajar; Arafat, Muhammad Rusli (Fakultas Hukum Universitas Sultan Ageng Tirtayasa, 2023)
Juvenile growth is a period when children have a high level of curiosity which sometimes leads them to commit crimes that can cause a high number of juvenile crimes. Juvenile criminal cases in Indonesia in 2020 reached 6,146 cases obtained from the 2020 Supreme Court Annual Report and in South Korea reached 38,590 cases obtained from the South Korean Judicial Yearbook 2020. There is a juvenile justice system to resolve juvenile criminal cases. This judicial system aims to educate and protect the rights of Children in Conflict with the Law (ABH) for their future. The juvenile justice system is regulated in Law Number 11 of 2012 concerning the Juvenile Criminal Justice System (UU SPPA) and the Juvenile Act in South Korea. A comparison of the juvenile justice system in the two countries in fostering and protecting juveniles is an interesting matter to discuss by paying attention to the statistics on juvenile crime, the juvenile justice system, types of punishment, and the laws that force in both countries. With normative legal research methods, conclusions are drawn regarding the significant differences in the judicial systems of the two countries.